2008
DOI: 10.1016/j.juro.2008.01.098
|View full text |Cite
|
Sign up to set email alerts
|

Stress Urinary Incontinence: Relative Importance of Urethral Support and Urethral Closure Pressure

Abstract: The finding that maximal urethral closure pressure and not urethral support is the factor most strongly associated with stress incontinence implies that improving urethral function may have therapeutic promise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
213
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(245 citation statements)
references
References 20 publications
20
213
1
6
Order By: Relevance
“…These increases in sphincter size appear to be clinically relevant; thickness and cross-sectional area both increased by ∼20 %, which is well above the estimated mean percent error of 12-15 %. Further, when improvements in continence are considered along with morphological changes, these results suggest that the training effect produced appears to be sufficient to overcome deficiencies in urethral pressure in women with SUI found by DeLancey's group [5,6].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These increases in sphincter size appear to be clinically relevant; thickness and cross-sectional area both increased by ∼20 %, which is well above the estimated mean percent error of 12-15 %. Further, when improvements in continence are considered along with morphological changes, these results suggest that the training effect produced appears to be sufficient to overcome deficiencies in urethral pressure in women with SUI found by DeLancey's group [5,6].…”
Section: Discussionmentioning
confidence: 77%
“…Interest grew when DeLancey et al reported that decreased urethral closure pressure is the factor most strongly associated with SUI [5,6]. This is supported by both morphological and electromyographic (EMG) evidence.…”
Section: Introductionmentioning
confidence: 99%
“…According to DeLancey and Asthon-Miller, damage of pelvic floor muscle and endopelvic fascia, the supportive layer under urethra, is related with delayed closure of urethral lumen (13,14). If abdominal pressure increase as in cough, urethra is displaced in a dorsocaudal line and the anterior edge of urethra move longer interval than posterior edge of urethra, so SUI would be occur (15).…”
Section: Discussionmentioning
confidence: 99%
“…1 This was a casecontrol study involving 103 women with SUI and 108 asymptomatic controls matched for age, race, parity and hysterectomy. The key variables analyzed were maximum urethral closure pressure (MUCP), urethral and pelvic organ support, levator ani muscle function, and intravesical pressure.…”
Section: Rose Studymentioning
confidence: 99%